NEED ASSESSMENT METODE PEMBELAJARAN PADA PERKULIAHAN STATISTIK PENELITIAN PENDIDIKAN DIMASA COVID-19 - Wardana, Rendy Wikrama; Mayub, Afrizal (EduFisika: Jurnal Pendidikan Fisika, 2021)
The study aims to describe the need for appropriate learning methods in educational research statistics lectures in the Covid-19 era. The type of research used was descriptive quantitative. The research sample amounted to 59 students consisting of 20 students from the master's degree program in science education and 39 students from the bachelor's program in physics education at one of the State Universities in Bengkulu City. The research instrument was a student response questionnaire consisting of 8 question items. Data collection was done through the distribution of questionnaires via google form. Data analysis was performed with descriptive statistics. The results of the study show that the Scafolding learning method is an alternative learning method in the era of covid 19. In addition, educational research statistics lectures have difficult and complex characteristics, especially in the data analysis process. Â